2018
DOI: 10.1016/j.cca.2018.09.039
|View full text |Cite
|
Sign up to set email alerts
|

An ELISA for quantifying GPIHBP1 autoantibodies and making a diagnosis of the GPIHBP1 autoantibody syndrome

Abstract: Background: Autoantibodies against GPIHBP1, the endothelial cell transporter for lipoprotein lipase (LPL), cause severe hypertriglyceridemia (“GPIHBP1 autoantibodies syndrome”). Affected patients have low serum GPIHBP1 and LPL levels. We report the development of a sensitive and specific ELISA, suitable for routine clinical use, to detect GPIHBP1 autoantibodies in serum and plasma. Methods: Serum and plasma samples were added to wells of an ELISA plate that had been coated with recombinant human GPIHBP1. GPI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Chylomicronemia occasionally appears spontaneously, and some of these ''acquired'' cases are caused by GPIHBP1 autoantibodies (''GPIHBP1 autoantibody syndrome'') (Beigneux et al, 2017;Eguchi et al, 2019;Hu et al, 2017a;Kersten, 2017). This disorder was discovered fortuitously while characterizing a monoclonal antibody-based ELISA designed to measure plasma levels of GPIHBP1 (Beigneux et al, 2017;Miyashita et al, 2018a). In those studies, two plasma samples, both from patients with chylomicronemia, had abnormally low GPIHBP1 levels, and the GPIHBP1 levels remained low even after ''spiking'' the plasma samples with recombinant GPIHBP1.…”
Section: Chylomicronemia From Gpihbp1 Autoantibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chylomicronemia occasionally appears spontaneously, and some of these ''acquired'' cases are caused by GPIHBP1 autoantibodies (''GPIHBP1 autoantibody syndrome'') (Beigneux et al, 2017;Eguchi et al, 2019;Hu et al, 2017a;Kersten, 2017). This disorder was discovered fortuitously while characterizing a monoclonal antibody-based ELISA designed to measure plasma levels of GPIHBP1 (Beigneux et al, 2017;Miyashita et al, 2018a). In those studies, two plasma samples, both from patients with chylomicronemia, had abnormally low GPIHBP1 levels, and the GPIHBP1 levels remained low even after ''spiking'' the plasma samples with recombinant GPIHBP1.…”
Section: Chylomicronemia From Gpihbp1 Autoantibodiesmentioning
confidence: 99%
“…It will also be important to determine if immune complexes are present in the plasma of affected patients. The presence of immune complexes could have been overlooked by the ELISAs used to detect GPIHBP1 autoantibodies (Beigneux et al, 2017;Miyashita et al, 2018a).…”
Section: Chylomicronemia From Gpihbp1 Autoantibodiesmentioning
confidence: 99%
“…A diagnosis of the GPIHBP1 antibody syndrome in patients with hypertriglyceridemia fundamentally depends on documenting GPIHBP1 autoantibodies in serum or plasma. GPIHBP1 autoantibodies can be identified quite easily with an ELISA (35,82). Dilutions of serum or plasma are incubated on 96-well plates coated with recombinant GPIHBP1.…”
Section: Downloaded Frommentioning
confidence: 99%
“…After obtaining the informed consent, targeted exon sequencing was performed to investigate 36 lipid-related genes (LDLR, PCSK9, ApoB, LDLRAP1, ABCG5, ABCG8, LCAT, ABCA1, LPL, ApoC-II, ApoC-III, ApoA-V, GPIHBP1, LMF1, which was first reported by Kihara et al in 1989 3) . Recently, a monoclonal antibody against human GPIHBP1 in plasma was developed by Miyashita et al 4) , and autoimmune hyperchylomicronemia with anti-GPIHBP1 antibodies was reported by Beigneux AP et al in 2017 5) . GPIHBP1 is a glycolipid-modified anchor protein that resides on capillary endothelial cell membranes and plays a role in transporting LPL from outside the capillaries into the lumen of blood vessels.…”
Section: Introductionmentioning
confidence: 99%